2021
DOI: 10.1515/nanoph-2021-0299
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne-decorated microfiber based soliton and noise-like pulse generation

Abstract: Graphdiyne has an inborn band gap energy, where the minimal band gap is about from 0.46 to 1.22 eV, which shows great potential in ultrafast laser generation. In this work, we fabricate a graphdiyne-decorated microfiber and demonstrate its saturable absorption characteristics experimentally. This device is used as a saturable absorber to generate the conventional soliton and noise-like pulse in an erbium-doped mode-locked fiber laser. The conventional soliton with a spectral bandwidth of 2.45 nm can switch int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…GDY, regarded as a promising carbon material, has garnered particular attention in light-matter interactions by virtue of its tunable E g , high carrier mobility and large 𝜋-conjugation compared to most optical materials. [267,[292][293][294][295][296] In recent years, to further improve the NLO properties (e.g., laser modulation, [85] second harmonic generation (SHG), [136] stability, [58] Kerr nonlinearity [297] ) of GDY, comprehensive experimental exploration on NLO properties of functional GDY-based nanoarchitectures have been rapidly developed. For example, in 2022, Xu et al [136] reported on a PVP/tetraphenylethylene (TPE)-modified GDY nanocomposite film (PVP/TPE-GDY) that showed a favorable NLO SHG response.…”
Section: Nonlinear Photonicsmentioning
confidence: 99%
“…GDY, regarded as a promising carbon material, has garnered particular attention in light-matter interactions by virtue of its tunable E g , high carrier mobility and large 𝜋-conjugation compared to most optical materials. [267,[292][293][294][295][296] In recent years, to further improve the NLO properties (e.g., laser modulation, [85] second harmonic generation (SHG), [136] stability, [58] Kerr nonlinearity [297] ) of GDY, comprehensive experimental exploration on NLO properties of functional GDY-based nanoarchitectures have been rapidly developed. For example, in 2022, Xu et al [136] reported on a PVP/tetraphenylethylene (TPE)-modified GDY nanocomposite film (PVP/TPE-GDY) that showed a favorable NLO SHG response.…”
Section: Nonlinear Photonicsmentioning
confidence: 99%
“…The pump power is too high to hold on one soliton in quantity according to the theory of soliton area. Therefore, the single pulse usually can bear lower energy in some extent [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NLP has a wide spectrum and high peak power, which attracts the attention of researchers studying supercontinuum and high energy pulse generation 43 . Ma et al 44 fabricated graphene‐decorated microfiber and obtained NLP using it, which indicates the great potential of NLP. Li et al 45 obtained broadband NLP by dispersion and nonlinearity management in ytterbium‐doped fiber lasers.…”
Section: Introductionmentioning
confidence: 99%